2007
DOI: 10.1111/j.1440-1746.2007.05123.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of audio stimulation on gastric myoelectrical activity and sympathovagal balance in healthy adolescents and adults

Abstract: Gastric slow waves and the sympathovagal balance are more strongly affected by audio stimulation in adolescents than in adults. The test meal normalizes the audio stimulation-induced differences between the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…In this study, using the spectral analysis of the HRV, an established noninvasive method for the assessment of the autonomic functions, we reported a significant increase in LF/HF ratio, resulting from a combination of decreased HF and increased LF, with the cold stress. Similar autonomic mechanisms were also reported with other kinds of stress . It should be noted that the HRV reflects cardiac efferent activity; it is the vagal efferent signal from the brain to the cardiac branch.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In this study, using the spectral analysis of the HRV, an established noninvasive method for the assessment of the autonomic functions, we reported a significant increase in LF/HF ratio, resulting from a combination of decreased HF and increased LF, with the cold stress. Similar autonomic mechanisms were also reported with other kinds of stress . It should be noted that the HRV reflects cardiac efferent activity; it is the vagal efferent signal from the brain to the cardiac branch.…”
Section: Discussionsupporting
confidence: 80%
“…28 Chen et al reported that audio stimulation (noise) decreased percentage of normal gastric slow wave in adolescents in fasting state. 29 In addition, there was a significant increase in the instability coefficient of dominant frequency with the cold stress. This EGG parameter reflects the variation of the gastric slow wave frequency through the recording period.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…33 Besides low temperature, other psychophysiological stressors, including noise, arithmetic task, stroop color-word test, and horrifying movie showed similar inhibitory effects on gastric myoelectrical activity. [34][35][36] Improvement in impaired gastric slow waves with EA has been previously reported in both animals and humans. 13 EA at ST36 increased the regularity of gastric slow waves and the number of spike bursts in dogs.…”
Section: Discussionmentioning
confidence: 84%
“…The effect of stress on gastric slow waves was shown by Imai et al 32 who demonstrated an increase in tachygastria with a decrease in the normal slow waves induced by optokinetic motion sickness. Also, Chen et al 33 showed that audio stimulation (noise) impaired percentage of normal gastric slow wave in adolescents. In addition, Riezzo et al, 34 found similar effects on gastric slow waves by different forms of stress, such as cold water and arithmetic task.…”
Section: Discussionmentioning
confidence: 99%